The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fonc.2021.759053
|View full text |Cite
|
Sign up to set email alerts
|

18F-PSMA-1007 PET/CT Performance on Risk Stratification Discrimination and Distant Metastases Prediction in Newly Diagnosed Prostate Cancer

Abstract: ObjectiveTo evaluate the prediction performance of 18F-PSMA-1007 PET/CT and clinicopathologic characteristics on prostate cancer (PCa) risk stratification and distant metastatic prediction.Materials and MethodsA retrospective analysis was performed on 101 consecutively patients with biopsy or radical prostatectomy proved PCa who underwent 18F-PSMA-1007 PET/CT. The semi-quantitative analysis provided minimum, maximum and mean standardized uptake (SUVmin, SUVmax and SUVmean) of PCa. Association between clinicopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Thus, to reduce unnecessary prostate biopsies for tumor malignancy prediction, radiomics signatures provide a more objective and independent prediction scheme.Prior study found that the detection rate of distant metastasis for 18 F-PSMA PET/CT was higher between the PSA ≥ 30ng/mL and PSA ≥ 20ng/mL cohorts. The PET/CT parameter SUVmax difference between primary tumors and metastatic lesions in metastatic PCa patients with a higher prediction PSA level (i.e., > 29.01) ( 4 ). Therefore, benefiting populations in a nomogram based on PSA, metastatic status, and radiomics score may be more likely to be represented in patients with higher PSA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, to reduce unnecessary prostate biopsies for tumor malignancy prediction, radiomics signatures provide a more objective and independent prediction scheme.Prior study found that the detection rate of distant metastasis for 18 F-PSMA PET/CT was higher between the PSA ≥ 30ng/mL and PSA ≥ 20ng/mL cohorts. The PET/CT parameter SUVmax difference between primary tumors and metastatic lesions in metastatic PCa patients with a higher prediction PSA level (i.e., > 29.01) ( 4 ). Therefore, benefiting populations in a nomogram based on PSA, metastatic status, and radiomics score may be more likely to be represented in patients with higher PSA.…”
Section: Discussionmentioning
confidence: 99%
“…All participants included in the data analysis were evaluated using 18 F-PSMA-1007 PET/CT and had PSA values measured within 4 weeks prior to the imaging scan. Diagnosis of PCa proven through histological examination served as a reference for PET imaging analyses ( 4 , 24 ). Patients were excluded from the analysis if they 1) had received local or systemic treatment, 2) lacked histological examination proven diagnosis or PSA value, and 3) had incomplete imaging data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, PSMA is a promising and specific target for prostate adenocarcinoma imaging. In the past years, PSMA PET/CT has extremely improved the management of prostate adenocarcinoma when compared with conventional imaging, especially in the aspect of detecting metastatic spread and micrometastases ( 5 , 6 ). Furthermore, as a molecular imaging examination, the expression level of PSMA on PET/CT is positively correlated with tumor stage and grade ( 7 ), which could help urologists identify patients who may need more intensive treatment and tailor treatment regimes.…”
Section: Introductionmentioning
confidence: 99%